Penerapan Taksonomi Bloom Revisi untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis - Netriwati, Netriwati (Desimal: Jurnal Matematika, 2018)
The ability to understand students' concepts is important. But the ability to understand the concept of students does not grow without just passing on an action from a serious educator in dealing with this problem. Developing learning objectives in general is one of the right steps taken by educators in learning. Bloom Revision Taxonomy that researchers will use in developing learning objectives in this study. so this study aims to describe students' abilities in understanding concepts through Bloom Revision's taxonomy. This type of research uses a qualitative descriptive method to see students' understanding of concepts in the implementation of microteaching in accordance with taxonomic steps of the revised bloom on the Education of Mathematics students at UIN Raden Intan in the sixth semester. Data collection techniques are tests on the implementation of microteaching and interviews. Based on the results of the assessment seen in the results of the observation sheet on the implementation of the learning that the steps of Bloom's Taxonomy can be applied in accordance with the selected indicators and in general students have been able to understand mathematical concepts well. So it can be concluded that the application of Bloom Revised Taxonomy in learning can improve students' ability to understand concepts